There was a similar U-shaped nonlinear association between waist-to-height ratio and the risk of new-onset hypertension: findings from the CHNS - Wang, Zhenwei; Shi, Qian; Yan, Xuejiao; Tang, Junnan; Zhang, Jinying (Frontiers in Nutrition, 2023)
The association between waist-to-height ratio (WHtR) with hypertension has not been adequately explained, so in this study we sought to clarify the predictive role of WHtR on the incidence of hypertension as well as the potential nonlinear associations in the general population.In this large prospective cohort study, a total of 4,458 individuals from the China Health and Nutrition Survey (CHNS) were included in the analysis. Multivariate Cox regression analyses, subgroup analyses, receiver operator characteristic (ROC) and restricted cubic spline (RCS) analyses were used to examine the association of WHtR with the risk of new-onset hypertension.Results: Hypertension occurred in 32.8% of participants during the maximum six-year follow-up period. Compared with the group with lower WHtR, the group with higher WHtR had a higher incidence of hypertension (P < 0.001). Multivariate Cox regression analysis showed that the risk of hypertension was 1.45 times higher in the high WHtR group than in the low WHtR group, and that the risk of hypertension increased by 30.4% for every 0.1 unit increase in WHtR (P < 0.001). Subgroup analyses also validated the stratified associations between WHtR and the risk of new-onset hypertension in most subgroups (P < 0.05). ROC analyses also revealed that WHtR was superior to body mass index in predicting new-onset hypertension (AUC: 0.626 vs 0.607, P = 0.009). Further RCS analysis detected a nonlinear association between WHtR and risk of new-onset hypertension (P for nonlinearity < 0.001).WHtR was nonlinearly associated with the risk of new-onset hypertension in the general population.